Thermally Evaporated CdTe Films with Various Thicknesses for Optoelectronics Applications (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:There are numerous optoelectronic uses for semiconductor thin films II-VI. One such substance that has proven effective is cadmium telluride (CdTe).Materials and Methods:CdTe thin films were created by thermally vaporizing the material under a high vacuum and depositing them on glass substrates with different thicknesses (72, 80, and 88 nm) by using thermal evaporation technique.Results:According to the results of the XRD test, the thermally evaporated CdTe films are polycrystalline and have a cubic structure. From (AFM) is used to evaluate the morphology of the film demonstrating the good homogenous surface. From (UV) incresed of thickness of the material resulted in a concurrent increase in absorbance and a decrease in transmittance. The values of the direct energy gap calculated from the Tauc relation decreased from (3.60) to (3.42) eV with increased thickness. The surface energy loss function (SELF) and volume energy loss function (VELF) incresed when thickness incresed. The structural tests and energy gap values refer to fine particle size and the surface of the prepared films and can be candidates for optoelectronic applications.Conclusions:The X-ray diffraction (XRD) analysis revealed that the CdTe films exhibited a polycrystalline nature, characterized by a cubic crystal structure. A noticeable enhancement in the crystal structure was noticed as the thickness increased. The clear result of the scanning electronic microscopy is that homogeneously distributed crystal grain morphology was observed. The inference of SEM is consistent with the result of the XRD measurement.